2018
DOI: 10.5811/westjem.2018.4.36879
|View full text |Cite
|
Sign up to set email alerts
|

Simple Changes to Emergency Department Workflow Improve Analgesia in Mechanically Ventilated Patients

Abstract: IntroductionIn 2013 the Society for Critical Care Medicine (SCCM) published guidelines for the management of pain and agitation in the intensive care unit (ICU). These guidelines recommend using an analgesia-first strategy in mechanically ventilated patients as well as reducing the use of benzodiazepines. Benzodiazepines increase delirium in ICU patients thereby increasing ICU length of stay. We sought to determine whether a simple educational intervention for emergency department (ED) staff, as well as two si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Of the 11 community‐based studies, five (45%) were randomized controlled trials, 38,45‐48 one was cluster‐randomized, 43 one was quasi‐randomized (alternate weeks), 39 and the remaining four (36%) were pre‐post studies40‐42,44: two single‐site and two multi‐site with controls (one with randomized allocation to intervention, the other unclear). Of the 11 hospital‐based studies, seven were single site pre‐post comparisons, 49‐52,54,56,59 one was a two site pre‐post comparison without a control, 53 one was a multi‐site pre‐post with one site non‐randomly allocated to intervention, 57 one was a multi‐site with multiple interventions rolled out at different times (non‐uniformly) across sites, 58 and one was a qualitative study 55 . We summarize the study types in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 11 community‐based studies, five (45%) were randomized controlled trials, 38,45‐48 one was cluster‐randomized, 43 one was quasi‐randomized (alternate weeks), 39 and the remaining four (36%) were pre‐post studies40‐42,44: two single‐site and two multi‐site with controls (one with randomized allocation to intervention, the other unclear). Of the 11 hospital‐based studies, seven were single site pre‐post comparisons, 49‐52,54,56,59 one was a two site pre‐post comparison without a control, 53 one was a multi‐site pre‐post with one site non‐randomly allocated to intervention, 57 one was a multi‐site with multiple interventions rolled out at different times (non‐uniformly) across sites, 58 and one was a qualitative study 55 . We summarize the study types in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The single peer comparison study reporting absolute differences in proportion 45 resulted in a small change of 6%. Studies using workflow re‐direct nudges (time/cost saving) reported significant absolute changes in proportions ranging from 20% to 30% 54,57 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A list of these articles and the reasons for their exclusions are provided in Supplementary Appendix 2 . Ultimately, 15 articles that evaluated interventions to optimize prescribing were included ( Bourdeaux et al, 2014 ; Harewood et al, 2011 ; Isenberg et al, 2018 ; Lemiengre et al, 2018 ; Mafi et al, 2018 ; Malhotra et al, 2016 ; Meeker et al, 2014 ; Musgrove et al, 2018 ; O'Connor et al, 2009 ; Patel et al, 2018 ; Patel et al, 2017 ; Presseau et al, 2018 ; Sacarny et al, 2018 ; Shakespeare et al, 2019 ; Yadav et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only two of the interventions applied a sufficient array of recommended techniques to address all identified determinants, and only one of these interventions was effective. Regarding the effective intervention, Isenberg et al ( Isenberg et al, 2018 ) noted that emergency department practitioners may not be aware of new guidelines published around pain management for mechanically ventilated patients and that workflow inadequacies may be preventing optimal analgesic and benzodiazepine use. To build practitioners’ knowledge, they provided feedback on their current prescribing and instructions about how to follow the new guidelines.…”
Section: Resultsmentioning
confidence: 99%